(untitled) (Scientific journal of the Fergana State University, 2024)
Since the second half of the last century, many fish species have been acclimatized to the territory of the Fergana Valley. Among them, there are species that accidentally entered and later became invasive. Among these species there is also Hemiculter leucisculus, and the current status of this species is analyzed in the article from the morphoecological point of view.